Transformasi Pembelajaran Melalui Augmented Reality (AR) Dan Virtual Reality (VR): Inovasi Kurikulum yang Responsif Terhadap Era Digital - Moch Rizwan Aprilianto; Mutiara Rahmawati (Indo Publishing, 2025)
This research focuses on the transformation of learning through the use of Augmented Reality (AR) and Virtual Reality (VR) technologies in curriculum innovation in the digital era, using a case study at SMKN 1 Probolinggo. The background of this research is based on the urgent need for education to respond to 21st-century challenges through the integration of immersive, interactive, and contextual learning technologies. This research uses a qualitative descriptive approach with a case study. Data were collected through in-depth interviews, participant observation, and documentation, and analyzed using the Miles and Huberman interactive model. The results show that AR and VR technologies not only increase student motivation and understanding of the material but also encourage experiential learning and strengthen the link between the curriculum and the needs of the industrial world. In addition to pedagogical benefits, this study also uncovers implementation challenges such as device limitations, teacher readiness, and systemic integration within the curriculum. The implications of this research indicate that the success of technology-based learning innovations is determined not only by technical aspects, but also by institutional support, human resource training, and curriculum design that adapts to technological developments. This research is expected to serve as a reference for policymakers and education practitioners in developing relevant and transformative digital learning.